Pengaruh Business Process Management terhadap Kepuasan Pelanggan di era digital - Jeni Susyanti; Lailia Afifah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Rapid changes in the digital era require companies to continue to improve operational efficiency and effectiveness in order to maintain customer satisfaction. Business Process Management (BPM) exists as a systematic approach to analyzing, designing, implementing and monitoring business processes to produce optimal value for customers. This research aims to analyze the influence of BPM on customer satisfaction in the context of business digitalization. A quantitative method with a survey approach was used to collect data from 100 respondents consisting of operational managers and customers of digital companies. The research results show that BPM implementation significantly increases customer satisfaction through increasing service speed, quality consistency, and ease of digital access. These findings underscore the importance of BPM as a managerial strategy in the digital era to maintain customer loyalty.